2002
DOI: 10.1124/jpet.102.038620
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Mitochondrial Energetic Impairment in the Toxicity of Nimesulide to Hepatocytes

Abstract: We described the effects of nimesulide (N-[4-nitro-2-phenoxyphenyl]-methanesulfonamide) and its reduced metabolite in isolated rat hepatocytes. Nimesulide stimulated the succinatesupported state 4 respiration of mitochondria, indicating an uncoupling effect of the drug. Incubation of hepatocytes with nimesulide (0.1-1 mM) elicited a concentration-and time-dependent decrease in cell viability as assessed by lactate dehydrogenase leakage, a decrease of mitochondrial membrane potential as assessed by rhodamine 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…Dissipation of mitochondrial transmembrane potential is commonly associated with destabilization of the outer mitochondrial membrane, which leads to the release of cytochrome c and other proapoptotic mitochondrial proteins into the cytoplasmic compartment (14). In fact, cell survival depends on the maintenance of mitochondrial transmembrane potential because of its involvement in ATP synthesis and maintenance of oxidative phosphorylation (47,48). We observed that exposure to LfcinB resulted in a loss of mitochondrial transmembrane potential by Jurkat T leukemia cells.…”
Section: Discussionmentioning
confidence: 63%
“…Dissipation of mitochondrial transmembrane potential is commonly associated with destabilization of the outer mitochondrial membrane, which leads to the release of cytochrome c and other proapoptotic mitochondrial proteins into the cytoplasmic compartment (14). In fact, cell survival depends on the maintenance of mitochondrial transmembrane potential because of its involvement in ATP synthesis and maintenance of oxidative phosphorylation (47,48). We observed that exposure to LfcinB resulted in a loss of mitochondrial transmembrane potential by Jurkat T leukemia cells.…”
Section: Discussionmentioning
confidence: 63%
“…64 The toxicity of nimesulide to hepatocytes has been previously observed 65,66 which is attributed mainly to the nitro group in its structure. 67 After reduction, NiNH 2 exhibits reduced toxicity than nimesulide in hepatocytes because nimesulide is a powerful protonophoretic uncoupler and NAD(P)H oxidant. 67 In addition, NiNH 2 can completely suppress the uncoupling and NAD(P)H oxidant effects on mitochondria.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 99%
“…67 After reduction, NiNH 2 exhibits reduced toxicity than nimesulide in hepatocytes because nimesulide is a powerful protonophoretic uncoupler and NAD(P)H oxidant. 67 In addition, NiNH 2 can completely suppress the uncoupling and NAD(P)H oxidant effects on mitochondria. 68,69 In this study, the nitro group of nimesulide was reduced to amine first and then grafted onto HA, suggesting that HA-nimesulide might reduce the liver toxicity effects of free nimesulide.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 99%
“…Tang et al (2004) reported that the CYP3A4 isoform was primarily responsible for the hepatic metabolism of fipronil in humans. Therefore, to evaluate the effect of biotransformation on the toxicity of fipronil, some experiments were performed using hepatocytes that were isolated from the rats that were pretreated with proadifen, a classic inhibitor of cytochrome P450 (Anders and Mannering 1996;Bort et al 1998;Mingatto et al 2002;Somchit et al 2009). The interference of fipronil in the functioning of the mitochondrial electron transport chain in the isolated rat hepatocytes was monitored by measuring the oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%